2011
DOI: 10.1159/000330657
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced-MRI and Ultrasound Evaluation of Painful Shoulder in Patients after Stroke: A Pilot Study

Abstract: Background: Epidemiological and radiological studies have previously been performed to identify the possible causes of hemiplegic shoulder pain (HSP). Many different etiologies have been postulated, though no clear correlations have emerged, and a multifactorial pathogenesis of HSP has been proposed. Recently, two MRI-based studies have described different shoulder findings as possible causes of pain in chronic stroke survivors. Purpose: The aim of this study was to describe the structural abnormalities of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 56 publications
3
19
1
Order By: Relevance
“…Acute hemiplegics with subluxation (75%) were significantly more frequent than chronic hemiplegics with subluxation (15%). This agrees with previous reports that shoulder subluxation in hemiplegia is predominantly seen in the acute phase [23,26,27], which has been attributed to its self-limiting nature [27]. The subluxed hemiplegic shoulders were characterized by significantly higher raw USS score (approximately 4 abnormalities per subluxed shoulder) than the non – subluxed hemiplegic shoulders (about 2 abnormalities per non-subluxed shoulder), suggesting that presence of subluxation is associated with more soft tissue injuries.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Acute hemiplegics with subluxation (75%) were significantly more frequent than chronic hemiplegics with subluxation (15%). This agrees with previous reports that shoulder subluxation in hemiplegia is predominantly seen in the acute phase [23,26,27], which has been attributed to its self-limiting nature [27]. The subluxed hemiplegic shoulders were characterized by significantly higher raw USS score (approximately 4 abnormalities per subluxed shoulder) than the non – subluxed hemiplegic shoulders (about 2 abnormalities per non-subluxed shoulder), suggesting that presence of subluxation is associated with more soft tissue injuries.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous sonographic studies [2,9]. However, adhesive capsulitis was the dominant finding in some studies that examined hemiplegic shoulders with conventional arthrography [28], contrast enhanced MRI [26,27], and magnetic resonance arthrography [29]. This discrepancy between USS and other imaging techniques could potentially be addressed in future studies by combining all of the various sonographic methods of detecting adhesive capsulitis reported in English literature thus far [15,3034] in order to improve detection rate.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies of MR findings suggestive of adhesive capsulitis between stoke survivors with and without HSP reported that synovial capsule thickening, synovial capsule enhancement, and enhancement in the rotator cuff interval were more prominent in those with HSP [13,14]. Unlike these studies, our study conducting on shoulder subluxation found no more MR arthrography findings suggesting adhesive capsulitis in the HSP group.…”
Section: Discussioncontrasting
confidence: 89%